2013
DOI: 10.1002/ar.22764
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Angular Measurements of the Foot of Modern Humans: A Test of Morton'S Foot Types

Abstract: In his classic research, Morton established two functionally different configurations of the bipedal and non-bipedal primate foot: one optimized for stability, with a stiff longitudinal arch and adducted first metatarsal, and the other for compliance. Modern human feet were seen as conforming to the bipedal norm and variation from it as pathology, even though clinical evidence has been clear that variation from the norm of a stiff longitudinal arch or adducted first metatarsal exists. This study aims to docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
6
12
1
Order By: Relevance
“…This finding is in agreement with Lautzenheiser and Kramer [13] who reported a good correlation between medial and lateral arches (r = 0.79). Additionally, the CIA has the highest correlation coefficient with C1MA (r = -0.90) and C5MA (r = -0.84) in our study, which indicates its relative importance to the aches.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in agreement with Lautzenheiser and Kramer [13] who reported a good correlation between medial and lateral arches (r = 0.79). Additionally, the CIA has the highest correlation coefficient with C1MA (r = -0.90) and C5MA (r = -0.84) in our study, which indicates its relative importance to the aches.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the CIA has the highest correlation coefficient with C1MA (r = -0.90) and C5MA (r = -0.84) in our study, which indicates its relative importance to the aches. This finding is also supported by the findings of Lautzenheiser and Kramer [13]. The authors reported an excellent correlation between this angle and medial arch (r = -0.81) as well as the lateral arch (r = -0.94) [13].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The mean of the foot angles in the present study were between the values reported in previous studies with radiographs [8,[31][32][33][34][35][36] and skin markers during midstance of gait [37]. The variation across subjects (indicated by the standard deviation in Table 2) was with 14.38 slightly higher than the approximately 108 reported in the literature [8,[31][32][33]35,37,38].…”
Section: Discussioncontrasting
confidence: 48%
“…The variation across subjects (indicated by the standard deviation in Table 2) was with 14.38 slightly higher than the approximately 108 reported in the literature [8,[31][32][33]35,37,38]. The importance of the posture on foot angles can be indicated by the effect of the postures in relation to the variation of the foot angles across subjects (between subject standard deviation).…”
Section: Discussionmentioning
confidence: 74%